2017
DOI: 10.1080/13561820.2017.1287165
|View full text |Cite
|
Sign up to set email alerts
|

Changing student attitudes through interaction: Findings from an interprofessional workshop

Abstract: Healthcare professionals are increasingly expected to work in interprofessional teams. Students therefore need opportunities to learn and practise skills that will allow them to be effective team members when they enter the workforce. This article summarises an interprofessional learning experience for 289 undergraduate and graduate students representing 13 programmes in a College of Health Professions (CHP) at a US public university. The half-day workshop provided an opportunity for participants with no prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
3
3
0
1
Order By: Relevance
“…Differences in attitudes toward interprofessional learning, roles and interaction were not found among the students participating in IPE and non-IPE course. However, the students exposed to IPE were more favorably inclined towards interprofessional learning in addition to dentistry and nursing students generally, what corroborates previous studies (30). They held counteractive opinions about interprofessional interaction.…”
Section: Discussionsupporting
confidence: 88%
“…Differences in attitudes toward interprofessional learning, roles and interaction were not found among the students participating in IPE and non-IPE course. However, the students exposed to IPE were more favorably inclined towards interprofessional learning in addition to dentistry and nursing students generally, what corroborates previous studies (30). They held counteractive opinions about interprofessional interaction.…”
Section: Discussionsupporting
confidence: 88%
“…The co-curricular interprofessional education experience highlighted roles and responsibilities of members of the interprofessional team and resulted in improved scores on the TRR across students' program level, discipline and prior IPE experiences. These findings parallel results from relatively short (<6 hours) interactive interprofessional educational seminar experiences, which demonstrated positive changes in attitudes towards interprofessional learning and collaboration among undergraduate and graduate health professions students (Dahlgren et al, 2018;Gould et al, 2017;Mishoe et al, 2018;Wellmon et al, 2012). Previous research has demonstrated improvement in overall attitudes towards interprofessional education and collaborative practice is possible after IPE focused coursework and our findings highlight similar results with a shorter intervention (Hood et al, 2014;Lairamore et al, 2018;Ruebling et al, 2014).…”
Section: Attitudes Towards Teamworksupporting
confidence: 62%
“…This IPE program deliberately highlighted the patient voice, and the authentic learning opportunities enabled students from seven healthcare disciplines to apply advanced teamwork skills; appropriate and effective IP communication; patient/client centred practice; and articulate the contribution of IP practice to holistic patient care. The program was underpinned by the belief that optimal health outcomes are enabled by effective IP working relationships with learners, practitioners, patients and families (CIHC, 2010;Gould, Day and Barton, 2017).…”
Section: Discussionmentioning
confidence: 99%